Method for separating ammonia-containing mixed gas by using ionic liquid hollow fiber composite membrane

By coating the selection layer of ionic liquid and polymer on the hollow fiber membrane, an ionic liquid hollow fiber composite membrane is prepared, which solves the problems of high energy consumption and environmental pollution of the ammonia-containing gas in the prior art, and achieves high efficiency and stability The ammonia-containing mixed gas separation effect is suitable for industrial applications.

CN119406210AActive Publication Date: 2025-02-11INSTITUTE OF PROCESS ENGINEERING CHINESE ACADEMY OF SCIENCES
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411819714.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-02-11
Estimated Expiration
2044-12-11

AI Technical Summary

Technical Problem

The existing membrane separation technology has problems such as high energy consumption, low product value and environmental pollution when dealing with ammonia-containing gases, and lacks high-efficiency membrane materials and technologies suitable for industrial applications.

Method used

The ionic liquid hollow fiber composite membrane is prepared by coating the ionic liquid and polymer on the base layer of the porous hollow fiber to separate the ammonia-containing mixed gas. The membrane material consists of a select layer and a substrate. Through the action of ionic liquid ammonia sites, it preferentially passes through ammonia gas to achieve efficient separation.

Benefits of technology

It realizes efficient separation of ammonia-containing mixed gas, has high ammonia permeability, separation selectivity and good stability, and is suitable for the separation, purification and recycling of various ammonia-containing gases. It is easy to prepare on a large scale, easy to operate and have an environment friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure BDA0005182806960000031
    Figure BDA0005182806960000031
Patent Text Reader

Abstract

The invention discloses a method for separating ammonia-containing mixed gas by using an ionic liquid hollow fiber composite membrane, and belongs to the technical field of gas separation and purification. The ionic liquid hollow fiber composite membrane is prepared from ionic liquid, a polymer and a porous hollow fiber substrate, the prepared hollow fiber composite membrane is filled and packaged in an assembly, and the ionic liquid hollow fiber composite membrane assembly is placed in an ammonia-containing gas membrane separation device. Ammonia-containing mixed gas enters from the raw material side of the ionic liquid hollow fiber composite membrane assembly, ammonia gas preferentially penetrates through the hollow fiber membrane to be transmitted to the permeation side to be collected under the action of ionic liquid ammonia sites, and other gas is collected or discharged from the retentate side, so that efficient separation of the ammonia-containing mixed gas is realized. According to the method, membrane materials and assemblies are easy to prepare on a large scale, and the separation method has the advantages of simple process, convenience in operation, high efficiency, easiness in operation, environment friendliness and the like; the method and the technology are suitable for separation, purification and recovery of ammonia-containing gas such as synthetic ammonia purge gas, smelting plant tail gas, chemical vapor deposition furnace tail gas, melamine tail gas, urea plant emission tail gas, nitric acid plant tail gas and amino acid production tail gas, and are promising.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of gas separation, and in particular to a method for separating ammonia-containing mixed gas by using an ionic liquid hollow fiber composite membrane. Background Art

[0002] Ammonia (NH3), as a common chemical substance, can be used as a reaction substrate to participate in the complex synthesis of a variety of chemicals, such as synthetic fibers, antimicrobial agents, ammonium salts and fertilizers. At the same time, in recent years, NH3 has been widely regarded as an energy carrier due to its high hydrogen content. Therefore, the potential application of NH3 in energy conversion and industrial production is huge. However, it cannot be ignored that NH3 emitted into the atmosphere is prone to react with acidic substances (SOx, NOx, etc.) to form haze weather. Therefore, the separation and recovery of NH3-containing tail gas in industrial processes has become particularly important.

[0003] At present, solvent absorption is a common method for treating NH3-containing gases. However, there are some unavoidable problems such as high energy consumption, low final product value, and environmental pollution. Membrane technology has the advantages of small footprint, strong operability, and easy scalability, and is considered to be a promising alternative technology. However, the trade-off between the permeability and selectivity of polymer membranes limits its application, and it is necessary to develop high-performance membrane materials. At present, there are reports in the literature that developed membrane materials for ammonia separation, such as cellulose acetate, polydimethylsiloxane, polytetrafluoroethylene and other polymer membranes, inorganic membranes, mixed matrix membranes, etc. However, most of them focus on the preparation of laboratory flat membranes and the study of the permeability and ideal selectivity of pure ammonia separation. At present, there is a lack of efficient membrane materials and corresponding technologies for the separation of ammonia-containing mixed gases in industrial applications. The gas flux is inversely proportional to the thickness of the selective layer. The preparation of thin composite membranes is one of the effective ways to increase the flux. Due to the advantage of high packing density of hollow fiber membranes in the module, hollow fibers are usually selected as porous support substrates. Coating a thin selective layer on the porous support substrate can greatly increase the flux and is easy to prepare on a large scale. Therefore, the development of hollow fiber composite membranes and ammonia separation technology consisting of a selective layer and a porous hollow fiber support base membrane is of great application significance for the industrial application of membrane separation of NH3-containing gases.

[0004] The present invention uses a coating method to coat the ionic liquid and the polymer membrane liquid inside or outside the porous hollow fiber substrate layer, and the obtained ionic liquid hollow fiber composite membrane filaments are filled and sealed in pipe fittings to obtain an ionic liquid hollow fiber composite membrane assembly, which is used for the separation of ammonia-containing mixed gases from different gas sources. The ammonia-containing mixed gas enters from the raw material side of the ionic liquid hollow fiber composite membrane assembly, and the ammonia gas preferentially passes through the hollow fiber membrane to the permeate side under the action of the ionic liquid ammonia site, and the remaining gas is discharged from the retentate side, thereby achieving efficient separation of the ammonia-containing mixed gas. The membrane materials and components of this method are easy to prepare on a large scale, the separation process is simple and efficient, the operation is flexible, and the environment is friendly. This technology is particularly suitable for the separation, purification and recovery of various ammonia-containing gases, including tail gas from production processes such as synthetic ammonia relaxation gas, smelters, melamine, urea plants, nitric acid plants, and chemical vapor deposition furnaces. Summary of the invention

[0005] The purpose of the present invention is to provide a method for separating mixed ammonia-containing gases using an ionic liquid hollow fiber composite membrane in view of the lack of membrane materials and technologies for engineering applications in existing membrane separation of ammonia-containing gases. The membrane materials and components of the method are easy to prepare on a large scale, have a large flux and a high separation factor for ammonia, thereby achieving efficient separation and recovery of mixed ammonia-containing gases.

[0006] To achieve this object, the present invention adopts the following technical solutions:

[0007] The ionic liquid hollow fiber composite membrane in the method of the present invention is prepared from ionic liquid, polymer, and porous hollow fiber substrate. The prepared ionic liquid hollow fiber composite membrane is filled and packaged into a component. The ionic liquid hollow fiber composite membrane component is placed in an ammonia-containing gas membrane separation device. The ammonia-containing mixed gas enters from the raw material side of the ionic liquid hollow fiber composite membrane. Under the action of the ionic liquid ammonia site, the ammonia gas preferentially passes through the hollow fiber membrane to the permeate side, and the remaining gas is discharged from the retentate side, thereby realizing efficient separation of the ammonia-containing mixed gas. The details are as follows:

[0008] The ionic liquid hollow fiber composite membrane of the present invention is composed of a selection layer and a substrate. The substrate is a porous hollow fiber, and its material is polyvinylidene fluoride, polyvinyl chloride, and polyacrylonitrile; the selection layer is prepared by a functional ionic liquid and a block polyetheramide polymer in a certain proportion, and the mass percentage of the ionic liquid is 1-60%. The functional ionic liquid structural formula is as follows:

[0009]

[0010] In the structural formula, R is C n H 2n+1 (n is an integer, 0≤n≤8) or C n H 2nOH (n is an integer, 1≤n≤4), but is not limited to the above-mentioned imidazole cations; the anion X of the ionic liquid - Including NO3 - 、SCN - 、HSO4 - CF3COO - CF3SO3 - 、(CF3SO2)2N - 、Co(SCN)4 2- 、Li(NTf2)2 - , but not limited to the above anions;

[0011] In the ionic liquid hollow fiber composite membrane of the present invention, the ionic liquid and the polymer are first prepared into a membrane liquid, which is then coated on the porous hollow fiber base layer by internal coating or external coating. After air-drying and baking, the prepared ionic liquid hollow fiber composite membrane filaments are filled and sealed in a pipe to obtain an ionic liquid hollow fiber membrane assembly.

[0012] The ionic liquid hollow fiber composite membrane component of the present invention is installed in an ammonia-containing gas membrane separation device. The ammonia-containing mixed gas enters from the raw material side of the hollow fiber composite membrane component. Under the action of the ionic liquid sites, the ammonia gas is preferentially permeated and transmitted to the permeate side, and the remaining gas is discharged from the retentate side. The component has a high permeation flux and separation factor for ammonia gas.

[0013] The ionic liquid hollow fiber composite membrane of the present invention can separate ammonia-containing mixed gas with an ammonia concentration of 1.5-70%, and the remaining gases include one, two, three or more of air, nitrogen, hydrogen, methane and carbon dioxide, with an inlet pressure of 0.01-5MPa and a temperature of 10-120°C.

[0014] The present invention prepares an ionic liquid polymer selective layer on the surface of a hollow fiber membrane by a coating method. Under the action of the ionic liquid ammonia site, ammonia gas preferentially passes through the selective layer of the hollow fiber membrane to the permeation side, thereby realizing efficient separation of ammonia-containing mixed gas. Compared with the prior art, the ionic liquid hollow fiber composite membrane of the present invention has high ammonia permeability, separation selectivity and good stability. The method of using an ionic liquid hollow fiber composite membrane to separate ammonia-containing gas has the advantages of simple process, high separation efficiency, easy operation, and environmental friendliness. It can be used for the separation and purification of synthetic ammonia relaxation gas, smelter tail gas, chemical vapor deposition furnace tail gas, melamine tail gas, urea plant exhaust gas, nitric acid plant tail gas, amino acid production tail gas, etc., and is a very promising new technology for separation and recovery of ammonia-containing gas. DETAILED DESCRIPTION

[0015] The technical solution of the present invention is described in more detail below through specific embodiments, but the present invention is not limited to the following embodiments. Without departing from the scope described above, changes in implementation are included in the technical scope of the present invention.

[0016] Example 1

[0017] 1) Using ethanol / water (70wt% / 30wt%) as a mixed solvent, condense and reflux at 80°C to dissolve Pebax 1657 particles, and stir for 4 hours to obtain a Pebax 1657 membrane solution with a concentration of 3wt%. Weigh the ionic liquid [Eim][NTf2] and add it to the above Pebax 1657 membrane solution, stir at room temperature for 2 hours, and obtain a [Eim][NTf2] / Pebax1657 membrane solution with a mass fraction of 15% of the ionic liquid.

[0018] 2) Apply the above membrane liquid to polyvinylidene fluoride (PVDF) hollow fiber membrane filaments, dry them in an oven at 60°C to obtain 15wt% [Eim][NTf2] / Pebax 1657 / PVDF ionic liquid hollow fiber composite membrane filaments; further fill and package the membrane filaments in pipes to prepare 15wt% [Eim][NTf2] / Pebax1657 / PVDF ionic liquid hollow fiber composite membrane components.

[0019] 3) The prepared 15wt% [Eim][NTf2] / Pebax 1657 / PVDF ionic liquid hollow fiber composite membrane module was installed and connected to an ammonia gas membrane separation device and a separation test was performed. The feed gas was a 1.5% / 98.5% NH3 / N2 mixed gas, the feed side pressure was 0.15MPa, the temperature was room temperature, and the ammonia in the feed gas preferentially passed through the ionic liquid hollow fiber composite membrane to the permeate side; the gas concentration on the permeate side and the gas concentration on the retentate side were detected by gas chromatography, and the gas permeation flux and separation factor were calculated, and the tail gas was absorbed by the sulfuric acid solution.

[0020] 4) The separation performance of the 15wt% [Eim][NTf2] / Pebax 1657 / PVDF ionic liquid hollow fiber composite membrane for 1.5% / 98.5% NH3 / N2 mixed gas is as follows: NH3 permeation flux is 114.7GPU, and NH3 / N2 separation factor is 103.2.

[0021] Example 2

[0022] 1) Using ethanol / water (70wt% / 30wt%) as a mixed solvent, condense and reflux at 80°C to dissolve Pebax 1657 particles, and stir for 4 hours to obtain a Pebax 1657 membrane solution with a concentration of 3wt%. Weigh the ionic liquid [Eim][NTf2] and add it to the above Pebax 1657 membrane solution, stir at room temperature for 2 hours, and obtain a [Eim][NTf2] / Pebax1657 membrane solution with a mass fraction of 15% of the ionic liquid.

[0023] 2) Apply the above membrane liquid to PVDF hollow fiber membrane filaments, dry them in an oven at 60°C to obtain 15wt% [Eim][NTf2] / Pebax 1657 / PVDF ionic liquid hollow fiber composite membrane filaments; further fill and package the membrane filaments in pipes to prepare 15wt% [Eim][NTf2] / Pebax 1657 / PVDF ionic liquid hollow fiber composite membrane components.

[0024] 3) The prepared 15wt% [Eim][NTf2] / Pebax 1657 / PVDF ionic liquid hollow fiber composite membrane module was installed and connected to an ammonia gas membrane separation device and a separation test was performed. The feed gas was a 50% / 50% NH3 / N2 mixed gas, the feed side pressure was 0.2MPa, the temperature was room temperature, and the ammonia in the feed gas preferentially passed through the ionic liquid hollow fiber composite membrane to the permeate side; the gas concentration on the permeate side and the gas concentration on the retentate side were detected by gas chromatography, and the gas permeation flux and separation factor were calculated, and the tail gas was absorbed by the sulfuric acid solution.

[0025] 4) The separation performance of the 15wt% [Eim][NTf2] / Pebax 1657 / PVDF ionic liquid hollow fiber composite membrane for a 50% / 50% NH3 / N2 mixed gas is: NH3 permeation flux is 330GPU, and NH3 / N2 separation factor is 72.

[0026] Example 3

[0027] 1) Using ethanol / water (70wt% / 30wt%) as a mixed solvent, condense and reflux at 80°C to dissolve Pebax 1657 particles, and stir for 4 hours to obtain a Pebax 1657 membrane solution with a concentration of 3wt%. Weigh the ionic liquid [Eim][NTf2] and add it to the above Pebax 1657 membrane solution, stir at room temperature for 2 hours, and obtain a [Eim][NTf2] / Pebax1657 membrane solution with a mass fraction of 15% of the ionic liquid.

[0028] 2) Apply the above membrane liquid to PVDF hollow fiber membrane filaments, dry them in an oven at 60°C to obtain 15wt% [Eim][NTf2] / Pebax 1657 / PVDF ionic liquid hollow fiber composite membrane filaments; further fill and package the membrane filaments in pipes to prepare 15wt% [Eim][NTf2] / Pebax 1657 / PVDF ionic liquid hollow fiber composite membrane components.

[0029] 3) The prepared 15wt% [Eim][NTf2] / Pebax 1657 / PVDF ionic liquid hollow fiber composite membrane module was installed and connected to an ammonia gas membrane separation device and a separation test was performed. The feed gas was a 15% / 25% / 60% NH3 / H2 / N2 mixed gas, the feed side pressure was 0.2MPa, the temperature was room temperature, and the ammonia in the feed gas preferentially passed through the ionic liquid hollow fiber composite membrane to the permeate side; the gas concentration on the permeate side and the gas concentration on the retentate side were detected by gas chromatography, and the gas permeation flux and separation factor were calculated, and the tail gas was absorbed by the sulfuric acid solution.

[0030] 4) The separation performance of the 15wt% [Eim][NTf2] / Pebax 1657 / PVDF ionic liquid hollow fiber composite membrane for a 15% / 25% / 60% NH3 / H2 / N2 mixed gas is as follows: NH3 permeation flux is 261.6GPU, and NH3 / N2 separation factor is 74.7.

[0031] Example 4

[0032] 1) Using anhydrous ethanol as solvent, condense and reflux at 80°C to dissolve Pebax 2533 particles, and stir for 4 hours to obtain a Pebax 2533 membrane solution with a concentration of 2wt%. Weigh the ionic liquid [Bim][NTf2] and add it to the above Pebax 2533 membrane solution, stir at room temperature for 2 hours, and obtain a [Bim][NTf2] / Pebax 2533 membrane solution with a mass fraction of 50% of the ionic liquid.

[0033] 2) The polyvinyl chloride (PVC) hollow fiber membrane was filled and packaged in a pipe to obtain a hollow fiber membrane module. The above membrane liquid was applied to the PVC hollow fiber membrane and dried in an oven at 60°C to obtain a 50wt% [Bim][NTf2] / Pebax2533 / PVC ionic liquid hollow fiber composite membrane module.

[0034] 3) The prepared 50wt% [Bim][NTf2] / Pebax 2533 / PVC ionic liquid hollow fiber composite membrane assembly was installed and connected to an ammonia gas membrane separation device and a separation test was performed. The feed gas was a 1.5% / 98.5% NH3 / N2 mixed gas, the feed side pressure was 0.3MPa, the temperature was room temperature, and the ammonia in the feed gas preferentially passed through the ionic liquid hollow fiber composite membrane to the permeate side; the gas concentration on the permeate side and the gas concentration on the retentate side were detected by gas chromatography, and the gas permeation flux and separation factor were calculated, and the tail gas was absorbed by the sulfuric acid solution.

[0035] 4) The separation performance of the 50wt% [Bim][NTf2] / Pebax 2533 / PVC ionic liquid hollow fiber composite membrane for 1.5% / 98.5% NH3 / N2 mixed gas is: NH3 permeation flux is 200GPU, and NH3 / N2 separation factor is 92.

[0036] Example 5

[0037] 1) Using anhydrous ethanol as solvent, condense and reflux at 80°C to dissolve Pebax 2533 particles, and stir for 4 hours to obtain a Pebax 2533 membrane solution with a concentration of 2wt%. Weigh the ionic liquid [Bim][NTf2] and add it to the above Pebax 2533 membrane solution, stir at room temperature for 2 hours, and obtain a [Bim][NTf2] / Pebax 2533 membrane solution with a mass fraction of 50% of the ionic liquid.

[0038] 2) The PVC hollow fiber membrane was filled and packaged in a pipe to obtain a hollow fiber membrane assembly. The above membrane liquid was applied to the PVC hollow fiber membrane and dried in an oven at 60° C. to obtain a 50 wt% [Bim][NTf2] / Pebax 2533 / PVC ionic liquid hollow fiber composite membrane assembly.

[0039] 3) The prepared 50wt% [Bim][NTf2] / Pebax 2533 / PVC ionic liquid hollow fiber composite membrane module was installed and connected to an ammonia gas membrane separation device and a separation test was performed. The feed gas was a 10% / 90% NH3 / N2 mixed gas, the feed side pressure was 0.2MPa, the temperature was room temperature, and the ammonia in the feed gas preferentially passed through the ionic liquid hollow fiber composite membrane to the permeate side; the gas concentration on the permeate side and the gas concentration on the retentate side were detected by gas chromatography, and the gas permeation flux and separation factor were calculated, and the tail gas was absorbed by the sulfuric acid solution.

[0040] 4) The separation performance of the 50wt% [Bim][NTf2] / Pebax 2533 / PVC ionic liquid hollow fiber composite membrane for 10% / 90% NH3 / N2 mixed gas is: NH3 permeation flux is 215GPU, and NH3 / N2 separation factor is 90.

[0041] Example 6

[0042] 1) Using anhydrous ethanol as solvent, condense and reflux at 80°C to dissolve Pebax 2533 particles, and stir for 4 hours to obtain a Pebax 2533 membrane solution with a concentration of 2wt%. Weigh the ionic liquid [Bim][NTf2] and add it to the above Pebax 2533 membrane solution, stir at room temperature for 2 hours, and obtain a [Bim][NTf2] / Pebax 2533 membrane solution with a mass fraction of 50% of the ionic liquid.

[0043] 2) The PVC hollow fiber membrane was filled and packaged in a pipe to obtain a hollow fiber membrane assembly. The above membrane liquid was applied to the PVC hollow fiber membrane and dried in an oven at 60° C. to obtain a 50 wt% [Bim][NTf2] / Pebax 2533 / PVC ionic liquid hollow fiber composite membrane assembly.

[0044] 3) The prepared 50wt% [Bim][NTf2] / Pebax 2533 / PVC ionic liquid hollow fiber composite membrane module was installed and connected to an ammonia gas membrane separation device and a separation test was performed. The feed gas was a 50% / 50% NH3 / N2 mixed gas, the feed side pressure was 0.2MPa, the temperature was room temperature, and the ammonia in the feed gas preferentially permeated the ionic liquid hollow fiber composite membrane to the permeate side; the gas concentration on the permeate side and the gas concentration on the retentate side were detected by gas chromatography, and the gas permeation flux and separation factor were calculated, and the tail gas was absorbed by the sulfuric acid solution.

[0045] 4) The separation performance of the 50wt% [Bim][NTf2] / Pebax 2533 / PVC ionic liquid hollow fiber composite membrane for a 50% / 50% NH3 / N2 mixed gas is as follows: NH3 permeation flux is 337GPU, and NH3 / N2 separation factor is 89.6.

[0046] Example 7

[0047] 1) Using ethanol / water (70wt% / 30wt%) as a mixed solvent, condense and reflux at 80°C to dissolve Pebax 1657 particles, and stir for 4 hours to obtain a Pebax 1657 membrane solution with a concentration of 1wt%. Weigh the ionic liquid [Im][NTf2] and add it to the above Pebax 1657 membrane solution, stir at room temperature for 2 hours, and obtain a [Im][NTf2] / Pebax 1657 membrane solution with a mass fraction of 50% of the ionic liquid.

[0048] 2) The PVC hollow fiber membrane was filled and packaged in a pipe to obtain a hollow fiber membrane assembly. The above membrane liquid was applied to the PVC hollow fiber membrane and dried in an oven at 60° C. to obtain a 50wt% [Im][NTf2] / Pebax 1657 / PVC ionic liquid hollow fiber composite membrane assembly.

[0049] 3) The prepared 50wt% [Im][NTf2] / Pebax 1657 / PVC ionic liquid hollow fiber composite membrane module was installed and connected to an ammonia gas membrane separation device and a separation test was performed. The feed gas was a 50% / 50% NH3 / N2 mixed gas, the feed side pressure was 0.2MPa, the temperature was room temperature, and the ammonia in the feed gas preferentially passed through the ionic liquid hollow fiber composite membrane to the permeate side; the gas concentration on the permeate side and the gas concentration on the retentate side were detected by gas chromatography, and the gas permeation flux and separation factor were calculated, and the tail gas was absorbed by the sulfuric acid solution.

[0050] 4) The separation performance of the 50wt% [Im][NTf2] / Pebax 1657 / PVC ionic liquid hollow fiber composite membrane for a 50% / 50% NH3 / N2 mixed gas is: NH3 permeation flux is 234.3GPU, and NH3 / N2 separation factor is 50.

[0051] Example 8

[0052] 1) Using ethanol / water (70wt% / 30wt%) as a mixed solvent, condense and reflux at 80°C to dissolve Pebax 1657 particles, and stir for 4 hours to obtain a Pebax 1657 membrane solution with a concentration of 1wt%. Weigh the ionic liquid [Bim][NO3] and add it to the above Pebax 1657 membrane solution, stir at room temperature for 2 hours, and obtain a [Bim][NO3] / Pebax 1657 membrane solution with a mass fraction of 35% of the ionic liquid.

[0053] 2) The PVC hollow fiber membrane was filled and packaged in a pipe to obtain a hollow fiber membrane assembly. The above membrane liquid was applied to the PVC hollow fiber membrane and dried in an oven at 60°C to obtain a 35wt% [Bim][NO3] / Pebax 1657 / PVC ionic liquid hollow fiber composite membrane assembly.

[0054] 3) The prepared 35wt% [Bim][NO3] / Pebax 1657 / PVC ionic liquid hollow fiber composite membrane assembly was installed and connected to an ammonia gas membrane separation device and a separation test was performed. The feed gas was a 10% / 90% NH3 / N2 mixed gas, the feed side pressure was 0.2MPa, the temperature was room temperature, and the ammonia in the feed gas preferentially permeated the ionic liquid hollow fiber composite membrane to the permeate side; the gas concentration on the permeate side and the gas concentration on the retentate side were detected by gas chromatography, and the gas permeation flux and separation factor were calculated, and the tail gas was absorbed by the sulfuric acid solution.

[0055] 4) The separation performance of the 35wt% [Bim][NO3] / Pebax 1657 / PVC ionic liquid hollow fiber composite membrane for 10% / 90% NH3 / N2 mixed gas is: NH3 permeation flux is 54.3GPU, and NH3 / N2 separation factor is 21.6.

[0056] Example 9

[0057] 1) Using ethanol / water (70wt% / 30wt%) as a mixed solvent, condense and reflux at 80°C to dissolve Pebax 1657 particles, and stir for 4 hours to obtain a Pebax 1657 membrane solution with a concentration of 1wt%. Weigh the ionic liquid [Bim][NO3] and add it to the above Pebax 1657 membrane solution, stir at room temperature for 2 hours, and obtain a [Bim][NO3] / Pebax 1657 membrane solution with a mass fraction of 50% of the ionic liquid.

[0058] 2) The PVC hollow fiber membrane was filled and packaged in a pipe to obtain a hollow fiber membrane assembly. The above membrane liquid was applied to the PVC hollow fiber membrane and dried in an oven at 60°C to obtain a 50wt% [Bim][NO3] / Pebax 1657 / PVC ionic liquid hollow fiber composite membrane assembly.

[0059] 3) The prepared 50wt% [Bim][NO3] / Pebax 1657 / PVC ionic liquid hollow fiber composite membrane module was installed and connected to an ammonia gas membrane separation device for testing. The feed gas was a 50% / 50% NH3 / N2 mixed gas, the feed side pressure was 0.2MPa, the temperature was room temperature, and the ammonia in the feed gas preferentially permeated the ionic liquid hollow fiber composite membrane to the permeate side; the gas concentration on the permeate side and the gas concentration on the retentate side were detected by gas chromatography, and the gas permeation flux and separation factor were calculated, and the tail gas was absorbed by the sulfuric acid solution.

[0060] 4) The separation performance of the 50wt% [Bim][NO3] / Pebax 1657 / PVC ionic liquid hollow fiber composite membrane for a 50% / 50% NH3 / N2 mixed gas is as follows: NH3 permeation flux is 210.7GPU, and NH3 / N2 separation factor is 45.8.

[0061] Example 10

[0062] 1) Using ethanol / water (70wt% / 30wt%) as a mixed solvent, condense and reflux at 80°C to dissolve Pebax 1657 particles, and stir for 4 hours to obtain a Pebax 1657 membrane solution with a concentration of 1wt%. Weigh the ionic liquid [Bim][TfO] and add it to the above Pebax 1657 membrane solution, stir at room temperature for 2 hours, and obtain a [Bim][TfO] / Pebax 1657 membrane solution with a mass fraction of 40% of the ionic liquid.

[0063] 2) The PVC hollow fiber membrane was filled and packaged in a pipe to obtain a hollow fiber membrane assembly. The above membrane solution was applied to the PVC hollow fiber membrane and dried in an oven at 60° C. to obtain a 40 wt% [Bim][TfO] / Pebax 1657 / PVC ionic liquid hollow fiber composite membrane assembly.

[0064] 3) The prepared 40wt% [Bim][TfO] / Pebax 1657 / PVC ionic liquid hollow fiber composite membrane assembly was installed and connected to an ammonia gas membrane separation device and a separation test was performed. The feed gas was a 50% / 50% NH3 / N2 mixed gas, the feed side pressure was 0.2MPa, the temperature was room temperature, and the ammonia in the feed gas preferentially permeated the ionic liquid hollow fiber composite membrane to the permeate side; the gas concentration on the permeate side and the gas concentration on the retentate side were detected by gas chromatography, and the gas permeation flux and separation factor were calculated, and the tail gas was absorbed by the sulfuric acid solution.

[0065] 4) The separation performance of the 40wt% [Bim][TfO] / Pebax 1657 / PVC ionic liquid hollow fiber composite membrane for a 50% / 50% NH3 / N2 mixed gas is as follows: NH3 permeation flux is 223.7GPU, and NH3 / N2 separation factor is 31.2.

Claims

1. A method for separating ammonia-containing mixed gas by using an ionic liquid hollow fiber composite membrane, characterized in that: The ionic liquid hollow fiber composite membrane is prepared from ionic liquid, polymer, and porous hollow fiber substrate. The prepared hollow fiber composite membrane is loaded and packaged into a component. The ionic liquid hollow fiber composite membrane component is placed in an ammonia-containing gas membrane separation device. The ammonia-containing mixed gas enters from the raw material side of the ionic liquid hollow fiber composite membrane. Under the action of the ionic liquid ammonia site, the ammonia gas preferentially passes through the hollow fiber membrane to the permeate side, and the remaining gas is discharged from the retentate side, thereby realizing efficient separation of the ammonia-containing mixed gas. The ionic liquid structural formula is as follows In the structural formula, R is C n H 2n+1 (n is an integer, 0≤n≤8) or C n H 2n OH (n is an integer, 1≤n≤4), but is not limited to the above-mentioned imidazole cations; the anion X of the ionic liquid - Including NO3 - 、SCN - 、HSO4 - CF3COO - CF3SO3 - 、(CF3SO2)2N - 、Co(SCN)4 2- and Li(NTf2)2 - , but not limited to the above anions; The polymer is a block polyether amide; The porous hollow fiber substrate is made of polyvinylidene fluoride, polyvinyl chloride, or polyacrylonitrile; The mass percentage of the ionic liquid in the ionic liquid hollow fiber composite membrane is 1-60%.

2. The method according to claim 1, characterized in that: In the ionic liquid hollow fiber composite membrane, the ionic liquid and the polymer membrane liquid are coated inside or outside on the porous hollow fiber substrate layer, and the ionic liquid hollow fiber composite membrane filaments are filled and sealed in a pipe to obtain an ionic liquid hollow fiber membrane assembly.

3. The method according to claim 1, characterized in that: The ionic liquid hollow fiber composite membrane module is placed in an ammonia gas membrane separation device. The ammonia mixed gas enters from the raw material side of the hollow fiber composite membrane module. Under the action of the ionic liquid sites, the ammonia gas preferentially permeates and is transmitted to the permeate side, and the remaining gas is discharged from the retentate side.

4. The method according to claim 1, characterized in that: The ionic liquid hollow fiber composite membrane separates ammonia in a mixed gas containing ammonia with an ammonia concentration of 1.5-70%, and the remaining gases include one, two, three or more of air, nitrogen, hydrogen, methane and carbon dioxide, with an inlet pressure of 0.01-5MPa and a temperature of 10-120°C.

5. The method according to claim 1, characterized in that: The ionic liquid hollow fiber composite membrane and assembly are suitable for separation, purification and recovery of different ammonia-containing gases, including synthetic ammonia purge gas, smelter tail gas, chemical vapor deposition furnace tail gas, melamine tail gas, urea plant exhaust gas, nitric acid plant tail gas, amino acid production tail gas, etc., and can achieve efficient separation and recovery of ammonia.

Citation Information

Patent Citations

  • Method for selectively separating ammonia gas by using multi-site proton type ionic liquid composite membrane

    CN111467933A

  • Method for separating ammonia and carbon through ionic liquid membrane

    CN113893709A

  • Preparation method and application of ionized polyimide gas separation membrane

    CN114797506A

  • Gas separation membrane

    CN115867376A

  • Polybenzimidazole hollow fiber membranes and method for making an asymmetric hollow fiber membrane

    US20160375410A1